Model Optimasi Penentuan Kombinasi Produk Menggunakan Metode Linear Programming pada Perusahaan Bidang Fashion - Marcella Marsetiani (Bina Nusantara University, 2014)
The aims of this research are to determine the most optimal method for sales forecasting, to show the number of sales forecast on March 2014, and to determine the appropriate and efficient product mix should be produced by PT Astakarya Busanaprima within the fashion industry. This research used six forecasting methods and linear programming technique by maximize function with eight decision variables: jackets, dresses, blouses, kebaya, caftans, skirts, pants, and shawls also with constrained factors: available time for work, primarily material, supporting material, and demand fluctuation. The results show that the best forecasting method for the company was linear regression which predicted that 17 jackets, 247 dresses, 78 blouses, 42 kebaya, 12 caftans, 15 skirts, 17 pants, and 4 shawls would be sold on March 2014. The appropriate and efficient product mix that should be produced on March 2014 are 17 jackets, 70 dresses, 78 blouses, 42 kebaya, 12 caftans, 15 skirts, 17 pants, and 4 shawls.